Replace, Repair, Restore, Relieve â_" Bridging Clinical and Engineering Solutions in Neurorehabilitation Proceedings of the 2nd International Conference on NeuroRehabilitation (ICNR2014), Aalborg, 24-26 June, 2014 - Jensen, Winnie; Andersen, Ole Kaeseler; Akay, Metin (Biosystems & Biorobotics, 2014)
The book is the proceedings of the 2nd International Conference on NeuroRehabilitation (ICNR 2014), held 24th-26th June 2014 in Aalborg, Denmark. The conference featured the latest highlights in the emerging and interdisciplinary field of neural rehabilitation engineering and identified important healthcare challenges the scientific community will be faced with in the coming years. Edited and written by leading experts in the field, the book includes keynote papers, regular conference papers, and contributions to special and innovation sessions, covering the following main topics: neuro-rehabilitation applications and solutions for restoring impaired neurological functions; cutting-edge technologies and methods in neuro-rehabilitation; and translational challenges in neuro-rehabilitation. Thanks to its highly interdisciplinary approach, the book will not only be a highly relevant reference guide for academic researchers, engineers, neurophysiologists, neuroscientists, physicians and physiotherapists working at the forefront of their field, but will also help to act as bridge between the scientific, engineering and medical communities. .